Stress Testing the USA - Short, J. author. aut Link
V, 203 p.
Keywords: In this volume, the USA is treated as a system that has been stress-tested by four unique events: the War on Terror, Hurricane Katrina, the Financial Meltdown that led to the Great Recession and the Giant Oil Spill. The author uses stress-testing to identify weaknesses within the "system," and examine the response to disaster.